INVESTIGATING INDONESIAN EFL TEACHERS’ PERCEPTIONS ON THE INTEGRATION OF ICT IN ENGLISH LANGUAGE LEARNING - Kristian Florensio Wijaya (ELTR Journal, 2022)
In this modern era, meaningful ELT enterprises cannot be detached from contextual ICT integration. It is strongly believed that the accurate internalization of ICT potentially promotes a more student-centered learning model where EFL learners can elevate their target language competencies to the utmost levels. This current small-scale qualitative study attempted to specifically investigate Indonesian EFL teachers’ perceptions on the integration of ICT in English language learning. To fulfill this research objectivity, 5 open-ended written narrative inquiry questions were administered to 2 experienced Indonesian EFL teachers possessing advanced technology skills. Based on the obtained research results, the further utilization of ICT in nowadays ELT processes since EFL learners have progressively transformed into more vigorous, autonomous, proactive, and proficient target language academicians. Concerning the significant advancement of this present study, future researchers are strongly encouraged to involve a greater number of Indonesian EFL teachers experiencing more variegated backgrounds in using ICT and incorporate a wide variety of research instruments to produce more generalizable research results.